2009
DOI: 10.1071/ea08265
|View full text |Cite
|
Sign up to set email alerts
|

Economic effects of alternate growth path, time of calving and breed type combinations across southern Australian beef cattle environments: feedlot finishing at the New South Wales experimental site

Abstract: Abstract. The 'Regional Combinations' project and its biophysical outcomes have been described in several other papers in this special edition. The information provided in these papers allows an evaluation of the most profitable beef cattle production systems across different environments in southern Australia. In this paper, the focus is on the New South Wales experimental site where the trial animals were finished in a feedlot. The data identified liveweight gain as the biggest driver of profitability of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Scope to alter carcass traits by nutritional management (manipulating growth rate after weaning) was also demonstrated. Although this produced fewer and smaller responses than by genetic means, it may have a large effect on enterprise profitability as discussed by Davies et al (2009) in a companion paper.…”
Section: Discussionmentioning
confidence: 99%
“…Scope to alter carcass traits by nutritional management (manipulating growth rate after weaning) was also demonstrated. Although this produced fewer and smaller responses than by genetic means, it may have a large effect on enterprise profitability as discussed by Davies et al (2009) in a companion paper.…”
Section: Discussionmentioning
confidence: 99%
“…At large production scales, technologies like ultrasonography can help to inform the decision-making process based on the composition of the carcass, but such technologies are usually not available to or feasible for small-scale farmers. Davies et al (2009) discussed the increase in costs caused by an increase in the feedlot time, when long periods are necessary to reach slaughter weight. These authors concluded that bulls with greater ADG require less time for finishing, and consequently generate lower production costs.…”
Section: Discussionmentioning
confidence: 99%
“…A higher pre-weaning growth rate and WW of beef calves is generally a key factor determining the profitability of beef production systems (Davies et al, 2009;Taylor et al, 2018). Calf pre-weaning growth was markedly different between the cow genotypes and is determined by both "maternal" (mainly due to milk production) and by direct genetic (growth capacity transmitted to calves) effects, as well as environmental factors (Cortés-Lacruz et al, 2017;Walmsley et al, 2018).…”
Section: Calf Performancementioning
confidence: 99%